THE IMPACT OF ACCESS TO TECHNOLOGY IN EDUCATION (Konferensiyalar | Conferences, 2024)
The technologies are gift to people. They are a sign of civilization. Because of technologies, life is becoming better and better day by day, as well as education system is also affected by them. The purpose of this article is to discuss the impacts of access to technology in education. Thanks to up-to-date technologies, at schools or universities, the way of learning and teaching is transforming. From interactive whiteboards to online platforms, technologies have an overwhelming influence on education landscape. The way of learning subjects, finding information on particular topic is becoming straightforward due to internet and gadgets like computers, phones. There is no more need to spend days or weeks in libraries, if you need some kind of data, only by searching internet or some platforms, you can acquire knowledge. Contemporary technologies have a vital role in every sphere of life. Several tasks can be automated. Students can receive individualized instructions tailored to their specific needs and learning styles. The author will conduct the survey and interview method as a consequence of this article. Overall, this paper argues that while technology offers immense potential to revolutionize education, its successful implementation requires a nuanced approach that addresses issues of equity, access, and responsible use. By critically examining both the opportunities and challenges, we can strive to create a future where technology serves as a catalyst for positive change and fosters inclusive, engaging, and effective learning environments for all.